Schooling and food: an analysis of pregnant teenagers from the Municipality of Cuité-PB (Research, Society and Development, 2020)
The level of education can influence eating habits and consequently impact on nutrient intake, thus considering the damage that such deficiencies can cause to the fetus and mother, the study aimed to evaluate the dietary intake of vitamin A and iron and its association with the schooling of pregnant adolescents in the municipality of Cuité-PB. This was a descriptive, cross-sectional research and quantitative methodological approach. The study included 15 pregnant adolescents attended at the prenatal service in Cuité-PB. The study showed a high prevalence of pregnant women diagnosed with overweight and level of education until incomplete high school. Regarding the consumption of vitamin A food sources, a reduced consumption of animal and plant foods was observed. Regarding iron consumption, there was low weekly liver intake and high daily consumption of beans, in addition to high weekly consumption of red meat. The results of the R24 applied indicate a predominance of inadequate vitamin A and dietary iron in the diet of frequent pregnant women, despite revealing consumption of some sources of these foods. Moreover, the study did not show a clear association with the occurrence of micronutrient inadequacies in food and education level, although the literature indicates a relationship between the level of education of pregnant women and their influence on self-care with health in general.